Electrical and spin switches in single‐molecule junctions - Guojun Ke; Chunhui Duan; Fei Huang; Xuefeng Guo (InfoMat, 2020)
Abstract Single‐molecule electrical and spin switches have been one of the main research focuses in molecular electronics and spintronics because they may form the most important elements for the future information technology, thus attracting great attention in the scientific community and witnessing significant progresses benefiting from the combination of physics, chemistry, materials, and engineering. The key issue of constructing single‐molecule switches is the development of stimulus‐responsive systems that provide bistable or multiple states. In this review, we summarize the recent advances of this field in terms of the external stimulus that induces the switching. A variety of external stimuli, such as light, electric field, magnetic field, mechanical force, and chemical stimulus, have been successfully employed to activate the reversible switching in single‐molecule junctions by manipulating molecular structures, conformations, electronic states, and spin states. As a burgeoning field, we finally put forward the challenges in molecular electronics and spintronics that need to be solved, which will initiate intense research.